PENGARUH INFLASI DAN SUKU BUNGA TERHADAP HARGA SAHAM PADA PT BANK CENTRAL ASIA TBK PERIODE 2018-2022 - Pasca Caroline Br Gurusinga; Fransiska Simanullang; Asmah Sinuraya (CV SWA Anugrah, 2023)
This research aims to determine the effect of inflation and interest rates on share prices at PT. Bank Central Asia, Tbk period 2018 - 2022 partially and simultaneously. The data analysis method used in this research is statistical analysis, using SPSS statistical software. This research analysis methodology continues with classical assumption testing and then ends with hypothesis testing. The classical assumption tests carried out include the normality test, multicollinearity test, heteriscedasticity test, and autocorrelation test. To carry out hypothesis testing, it is necessary to carry out T test and F test analysis. Based on the results of the Inflation research, it produces a calculated T value > T table with a value of 7.113 > 4.303 and a significance value of 0.019 < 0.05, it can be concluded that Inflation (X1) has an effect and partially significant to share prices. The interest rate produces a calculated T table with -6.332 < 4.303, and a significant value of 0.024 < 0.05. Based on these results, it can be concluded that partially interest rates have a negative and significant effect on share prices. The F test value is 27.038 > 9.55 with a significant value of 0.036 < 0.05. Based on these results, it is concluded that Inflation and Interest Rates simultaneously and significantly influence share prices at PT. Bank Central Asia, Tbk for the period 2018 - 2022.